Subsidence caused by high extraction coal mining in the Sasolburg and Secunda areas : prediction thereof and the mitigation of its effects - Van der Merwe, Jacob Nielen (My University, 1991)
The thesis describes the results of research which was done over the period 1985 to 1990 in the Sasolburg and Secunda areas into the effects of underground high extraction coal mining on the surface, surface structures and agriculture. Legal restrictions on the undermining of structures potentially sterilize more than 30% of the coal reserves in the study area. The basic motivation for doing the research was that most of the restrictions could be overcome if methods could be developed to undermine structures safely and economically. For subsidence data analysis, a computerised three dimensional method of analysis, the Surface Element Analysis (SEA) approach, was developed and implemented. Using the results of the analyses and analytical considerations, a subsidence profile prediction method was developed. The prediction method incorporates a new approach to the prediction of strain, based on the shape of the subsidence profile and the thickness of deformable layers on surface. The reactions of various commonly occurring structures in the study area, namely bituminised roads, gravel roads, pipe lines and conveyor belts, to subsidence were analysed. It was found that although no consideration to subsidence was given in the design of the structures, most could withstand the effects thereof safely with only minor and relatively inexpensive precautionary and repair measures. With regard to agriculture, it is shown that while there are mining induced effects, they are in general not severe. There is, however, reason for concern regarding the long term and not immediately apparent effects. Further work is thus very necessary. Overall, it was found that while a very cautious approach to high extraction undermining had merits in the past, most of the restrictions can be relaxed in the light of the knowledge which is now available. The important provision is that careful and detailed prior investigations are necessary for each individual case, and that a sound and responsible engineering approach must be followed. Mines can derive substantial economical benefit from the mitigation methods which are described. A very important aspect is the administrative handling of the undermining of structures. A coordinated multi disciplinary approach, catering for communication and joint planning of mining and infrastructure, is proposed. It contains the essential elements of the Australian approach with modifications for local South African conditions.
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: Coal mines and mining -- Environmental aspects.; Coal mines and mining -- Research.; Ground control (Mining); Mine subsidences.; Coal mines and mining -- Data processing.